A Large Cross-Sectional Community-Based Study of Newborn Care Practices in Southern Tanzania - Penfold, Suzanne; Hill, Zelee; Mrisho, Mwifadhi; Manzi, Fatuma; Tanner, Marcel; Mshinda, Hassan; Schellenberg, David; Armstrong Schellenberg, Joanna R. M. (PLOS ONE, 2010)
Despite recent improvements in child survival in sub-Saharan Africa, neonatal mortality rates remain largely unchanged. This study aimed to determine the frequency of delivery and newborn-care practices in southern Tanzania, where neonatal mortality is higher than the national average. All households in five districts of Southern Tanzania were approached to participate. Of 213,220 female residents aged 13–49 years, 92% participated. Cross-sectional, retrospective data on childbirth and newborn care practices were collected from 22,243 female respondents who had delivered a live baby in the preceding year. Health facility deliveries accounted for 41% of births, with nearly all non-facility deliveries occurring at home (57% of deliveries). Skilled attendants assisted 40% of births. Over half of women reported drying the baby and over a third reported wrapping the baby within 5 minutes of delivery. The majority of mothers delivering at home reported that they had made preparations for delivery, including buying soap (84%) and preparing a cloth for drying the child (85%). Although 95% of these women reported that the cord was cut with a clean razor blade, only half reported that it was tied with a clean thread. Furthermore, out of all respondents 10% reported that their baby was dipped in cold water immediately after delivery, around two-thirds reported bathing their babies within 6 hours of delivery, and 28% reported putting something on the cord to help it dry. Skin-to-skin contact between mother and baby after delivery was rarely practiced. Although 83% of women breastfed within 24 hours of delivery, only 18% did so within an hour. Fewer than half of women exclusively breastfed in the three days after delivery. The findings suggest a need to promote and facilitate health facility deliveries, hygienic delivery practices for home births, delayed bathing and immediate and exclusive breastfeeding in Southern Tanzania to improve newborn health.